Analysis of Coherence Between Linear and Cubic SBAS Displacement Models in Deformation Monitoring - Sefercik, Umut Güneş; Gorken, M.; Nazar, Mertcan (International Society for Photogrammetry and Remote Sensing, 2025)
Land reclamation projects are a common feature of coastal cities around the world and have been carried out for a number of different purposes. The rapid growth of the global population and the concomitant increase in socioeconomic developments have resulted in a corresponding rise in demand for air transportation services. The construction of airports on reclaimed areas may result in an increased susceptibility to ground subsidence, which could potentially lead to damage to the infrastructure and safety concerns for the public. Consequently, traditional ground deformation methodologies have been extensively employed in small-scale applications, although their spatial resolution is restricted and they require a considerable input of labor and time. In order to monitor ground deformation at reclaimed airports, interferometric synthetic aperture radar (InSAR) technology has become an invaluable tool. Furthermore, the small baseline subset (SBAS) method, a multi-temporal InSAR (MT-InSAR) approach, was developed for the periodic monitoring of ground deformation with sub-centimeter accuracy. This was achieved through the utilization of a SAR dataset with small baselines, thereby enhancing the quality of interferograms. The present study comprises a coherence analysis of linear and cubic SBAS displacement models, with ground deformation monitoring at Hatay Airport based on 151 Sentinel-1A single-look complex (SLC) SAR images acquired between 2 December 2017 and 29 January 2023. Consequently, the mean deformation velocity and the cumulative deformation values were determined in the satellite line-of-sight (LOS) direction. Cumulative vertical deformation maps were generated for both the linear and cubic SBAS displacement models, with values ranging from -142.71 mm to 60.11 mm and from - 224.84 mm to 69.9 mm, respectively. The coherence analysis yielded a standard deviation of ±8.525 mm after bias elimination, for the differences in cumulative vertical deformation between the linear and cubic SBAS displacement models. A cumulative vertical deformation difference map was ultimately constructed, with values ranging from -42 mm to 42 mm. © 2025 Elsevier B.V., All rights reserved.
2025 EARSeL and DGPF Joint Istanbul Workshop on Topographic Mapping from Space -- Istanbul -- 209677
Keywords: Coherence Analysis; Deformation Monitoring; Displacement Model; MT-InSAR; Reclamation Area; SBAS